KAJIAN KELUARGA tHALAssEMIA b-HEMOGLOBIN E - Nurul A; Adi K Aman; Ratna A G (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
HbE-b thalassemia is an inherited hemoglobin disorder of gene combination b thalassemia and HbE. It is caused by thalassemia and hemoglobinopathy gene,which acting as the allele in the same locus of chromosome. The clinical presentation is more severe than HbEhomozygote and almost similar to b thalassemia major. This disease is found predominantly in South East Asia, including Indonesia.The family study is very needed in order to genetic screening to prevent hemoglobinopathy and thalassemia homozygote. The objective ofthis study is to know the pedigree from the daughter who suffer from HbE- b thalassemia which is taken care in the children ward at H.Adam Malik Top Refferal Hospital, Medan. The family study was also done to both father and mother, one sister and to both grandparent.An examination was carried ,which include physical examination, complete cell blood count, peripheral blood morphology, hemoglobinanalysis with Hb-electroforese pH 8.5 agarose medium and read with densitometri, and osmotic fragility examination. From the familystudy was found that her father suffer from HbE heterozygote while the mother suffer from b thalassemia trait and sister got HbE- bthalassemia. The father and mother have no relative acceptance and there is no any blood linkage. Her grandparent could not performthe blood sample because they were have already passed away .